Pemulihan Semangat dan Ekspresi Diri Siswa Melalui Pendekatan Client-Centered - Donal Donal; Dea Safitri; Izzah Mardhiyah Murassyidah; Melinda Sari (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
This study aims to describe the application of a humanistic counseling approach (client-centered) in assisting students who experience a decline in life enthusiasm and self-expression due to social pressures at school. The research employed a descriptive qualitative method with a case study design involving a seventh-grade student who exhibited behavioral changes from being cheerful to withdrawn and apathetic. Data were collected through observation, in-depth interviews, and counseling reflection notes, validated through source triangulation. The results indicate that the implementation of empathy, unconditional positive regard, and reflection of feelings in individual, group, and classroom counseling effectively facilitated the student’s emotional recovery, fostered a positive self-concept, and enhanced learning motivation and self-expression. The client-centered approach proved effective in helping the student restore socio-emotional balance and rebuild self-confidence.